Application of biotechnology in genetic improvement, characterization and conservation of livestock - Rege, J.E.O. (University of Zimbabwe, 1995)
Among agricultural and allied fields, animal production and health have probably benefited the most from biotechnology. Successful application of biotechnology has generally been limited to developed countries. Specifically, there are hardly any success stories of the application of biotechnology in the improvement of livestock production in Africa. This paper reviews available biotechnologies with current and/or potential application in genetic improvement, characterization and/or conservation of domestic animal genetic resources and attempts to identify those technologies which have been, or may be, applied in developing countries.